Association between sleep, care burden, and related factors among family caregivers at home. Issue 4 (23rd January 2020) - Ryuno, Hirochika; Greiner, Chieko; Yamaguchi, Yuko; Fujimoto, Hirokazu; Hirota, Misato; Uemura, Hisayo; Iguchi, Hitoshi; Kabayama, Mai; Kamide, Kei
Abstract : Aim: Several studies have reported a negative correlation between depressive symptoms and family caregivers' (FCs) subjective sleep status. However, there is a paucity of information on the association between objective/subjective sleep status, care burden, and related factors. Methods: Participants were 23 pairs of care receivers (CRs; Mage = 82.7 ± 8.5 years; 69.6% women) receiving long‐term care at home and their FCs (Mage = 66.9 ± 11.0 years; 69.6% women). At baseline, demographic data, subjective sleep status (Pittsburgh Sleep Quality Index; PSQI), WHO‐5 well‐being, depressive mood, and frequency of going outdoors were collected. FCs wore a small, wrist‐worn device with an accelerometer to assess objective sleep status for a consecutive 24‐h 2‐week period, and they answered the Zarit Burden Interview short version (ZBI) every night before sleep. After 3 months, CR status was collected and analysed retrospectively. Results: The mean total sleep time over 2 weeks was 349.5 ± 69.6 min. The mean ZBI score over 2 weeks was 8.8 ± 6.8, which was significantly correlated with total sleep time (r = −0.42; P < 0.05), total time in bed (r = −0.44; P < 0.05), PSQI (r = 0.62; P < 0.01), frequency of going outdoors by CRs (r = −0.42; P < 0.05), and WHO‐5 well‐being among CRs (r = −0.50; P < 0.05). Multiple regression analyses revealed that total sleep time (β = −0.51; P < 0.05) was significantly associated with care burden (adjusted R 2 = 0.45). At the 3‐month follow‐up, four CRs had been hospitalised or died, and their FCs displayed significantly severe care burden and slept less than at baseline. Conclusions: Reduced objective total sleep time is significantly associated with the severity of care burden among FCs. Home‐based care is critical in Japan; therefore, it is meaningful to determine how to reduce care burden.